MENINGKATKAN MINAT BACA DENGAN MEDIA PERPUSTAKAAN DESA - Rahimah, Anni; Harahap, Sri Mahrani; Lubis, Mina Syanti; Lubis, Muhammad Sofyan; Simamora, Imam Samudra; Harahap, Riska Apriani (Institut Pendidikan Tapanuli Selatan, 2024)
Improving children's literacy activities and reading culture is very necessary in the current era of technological onslaught. So children's reading ability is greatly influenced by their interest in reading and their reading ability. Reading is an important activity in life because it can provide useful knowledge and information. Children in the village of Janji Mauli-MT come to the library because they still have minimal reading skills. We carry out this activity to provide motivation to children with the aim of increasing children's interest in reading by using village library media. The design of the mechanism for implementing PkM (Pengabdian kepada Masyarakat) or Community service activities was carried out by adopting action research steps which consisted of 3 (three) stages, namely: planning, action, observation and evaluation. To find out the results achieved during the two weeks of implementing PkM, a reading test was carried out to determine the extent of the child's abilities and progress. Has there been any improvement or not during the implementation of the PkM (Pengabdian kepada Masyarakat) or Community service activities? The results achieved from PkM activities in the village of Janji Mauli-MT. District Angkola Muaratais. namely, children in the village of Janji Mauli-MT can already recognize letters or the alphabet correctly and there has even been an improvement after implementing something called PkM (Pengabdian kepada Masyarakat) or Community service to increase children's interest in reading using the library media in the village of Janji Mauli-MT. .